Information sharing between different groups: a qualitative study of information service to business in Japanese public libraries - Shunsaku Tamura; Makiko Miwa; Yasunori Saito; Mika Koshizuka; Yumiko Kasai; Mamiko Matsubayashi; Nozomi Ikeya (Information Research: An International Electronic Journal)
Introduction. This paper is the first report of a research project on the effects of information service to business in Japanese public libraries. The overall goals of the project are to develop a conceptual framework for understanding effects of a library service and then to examine them in business information service. The objective of this first report is to get an overview of current practice of business information service in Japanese public libraries and examine images of users and uses by librarians in charge. Method. The project consists of three stages. At the first stage a series of field trips was conducted with semi-structured interviews in 22 libraries all over Japan and a focused group interview of librarians in charge of the service was also conducted (not reported here). Results. A variety of services are provided by public libraries. Levels of reference service and relationships with other agencies and organizations are the most important factors in determining the nature and kind of service provided. The process of providing the service is actually a complex process influenced by many factors. Conclusion. . Results suggest strongly the complex process of value creation. Images of users and uses are formed not only by direct contact with users but as a result of this complex process. Sometimes images have political connotations as both librarians and other stakeholders hope the service to be useful in promoting local business and/or industry and advancing local lives.